Energy projects in Iceland – Advancing the case for the use of economic valuation techniques to evaluate environmental impacts. (July 2016) - Cook, David; Davíðsdóttir, Brynhildur; Kristófersson, Daði Már
Abstract: Decision-making in Iceland has occurred without reference to economic valuations of the environmental impacts of energy projects. Environmental Impact Assessments, a legal requirement for nearly all energy projects in Iceland since 1994, have played an important role in identifying the environmental impacts of energy projects, and proposing mitigation measures. However, a purely qualitative description of environmental impacts is insufficient to ensure that they are accounted for equivalently with all of the other costs and benefits of a proposed project. Instead, as monetary information concerning the welfare gains or losses of proposed projects is not currently required to be provided to the licensing body, Orkustofnun, there is the potential for sub-optimal decision-making to occur. As this paper sets out, a broad variety of non-market valuation techniques already exist and could be applied to estimate the value of environmental benefits sacrificed to accommodate such developments. These methods and their outcomes could be incorporated within mandatory cost-benefit assessments for proposed Icelandic energy projects, communicating an estimate of the full welfare implications of approvals to decision-makers and the public alike, and fulfilling an OECD demand for the country to commence such processes. Highlights: Current risk of sub-optimal decision-making by licensing body, Orkustofnun. OECD call for monetary valuations of environmental impacts linked to Icelandic energy projects. Lessons to be learned from US regulatory approach to advance cost-benefit assessment practice in Iceland. Practice of conducting non-market valuation techniques limited in Iceland, but now growing.